The Effects of Explicit Scientific Argumentation Instruction through Practical Work on Science Process Skills - Ping, Irene Lue Leh; Halim, Lilia; Osman, Kamisah (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2019)
The aim of this study was to investigate the effects of incorporating explicit instruction of scientific argumentation through practical work on 10th grade students’ skills in science process. This research used a quasi-experimental method which involved one control group and two experimental groups from two national secondary schools in the category of rural school were involved in this study. A total of 112 10th grade students from the three classrooms were assigned randomly as the conventional (CON) group, experimental group with Inquiry without Argument approach (IWA) group and the Modified Argument-Driven Inquiry approach (MADI) group. In order to evaluate the effects of intervention on the tenth-grade students, Science Process Skills Test (SPS Test) was administered as pre-test and post-test on the control and experimental groups. Data collected from the experimental study were described by means of descriptive analysis and inferential analysis involving ANOVA analyses. The results of ANOVA showed there exist significant differences in science process skills among the three groups where students in the MADI group showed better performance compared to the other groups. The results of this research have implication on researchers and practitioners keen on promoting biology science process skills through instructions of scientific argumentations given explicitly in learning environments of science practical work.